Coping with childhood trauma: the unnamed narrator's defense mechanisms in Neil Gaiman's The Ocean at the End of the Lane (2013) - Ong, Li Yuan; Ali Termizi, Arbaayah (Universiti Putra Malaysia Press, 2018)
Neil Gaiman, a well-known British author, writes science fictions using various literary genres such as fantasy, horror and Norse mythology. Through the uses of various literary genres in his novels and short stories, Gaiman highlights the themes of childhood trauma and the character’s self-identity in The Ocean at the End of the Lane (2013). In this paper, the main protagonist’s struggles in coping with adulthood are interpreted using repression and denial as his primary defense mechanisms. These psychoanalytic concepts are believed to be means of ego defense to dismiss the unnamed male character’s childhood trauma. The character also undergoes repression and denial as the result of his inability to cope with his painful experiences during his childhood. In order to move on with his life, the unnamed character chooses to imagine and immerse himself into fantasy to lessen his painful experiences of the unpleasant incidents by internalizing his memories and dismiss them via repression as well denial. Hence, this paper argues that the concepts of repression and denial, as defense mechanisms, help the unnamed male character to cope with negative situations, which threatens his psychological condition during his childhood.